TEKNIK SELF MANAGEMENT UNTUK MENGATASI KECANDUAN GAME ONLINE - taufik, ismail (AflahConsilia : Jurnal Bimbingan dan Konseling, 2023)
This study aims to find out more about the phenomenon of online game addiction, and researchers apply counseling treatment with self management techniques. This research uses a qualitative approach with a case study type. While the counseling technique applied by researchers is using self management techniques. The results of this study indicate that there have been changes in the counselee, although not significant, but the counselee has been able to manage time starting to make a schedule and commit to the schedule agreed upon with the counselor. So that to get better results, time and follow-up are needed.